2020
DOI: 10.1108/tr-08-2019-0335
|View full text |Cite
|
Sign up to set email alerts
|

Luxury shopping tourism: views from Chinese post-1990s female tourists

Abstract: Purpose This study aims to explore how the concept of extended self-influences luxury shopping tourism consumption among Chinese tourists. It explores why luxury shopping is important for Chinese tourists. Specifically, this study focuses on a strategically important emerging market segment: post-1990s female Chinese tourists. Design/methodology/approach To explore the link between the extended self and luxury shopping tourism consumption among post-1990s Chinese female tourists, this study adopted a qualita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Therefore, understanding Chinese tourists’ shopping phenomenon has become crucial in retailing and tourism studies. Factors that motivate Chinese tourists to do shopping abroad have been identified, including, uniqueness, value for money (Hung et al , 2021), lower prices after tax (Li et al , 2020), high-quality and authentic products, extensive selection, enthusiastic service offerings (Wang et al , 2010), trustworthiness of product quality, the service quality of service providers, availability of the desired products, travel convenience in the destination (Ren and Hung, 2022), social interactions with staff and the shop environment (Lee and Choi, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, understanding Chinese tourists’ shopping phenomenon has become crucial in retailing and tourism studies. Factors that motivate Chinese tourists to do shopping abroad have been identified, including, uniqueness, value for money (Hung et al , 2021), lower prices after tax (Li et al , 2020), high-quality and authentic products, extensive selection, enthusiastic service offerings (Wang et al , 2010), trustworthiness of product quality, the service quality of service providers, availability of the desired products, travel convenience in the destination (Ren and Hung, 2022), social interactions with staff and the shop environment (Lee and Choi, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies (e.g., Chaney & Gamble, 2008;Smith et al, 2010) have also shown that women tend to have more favorable beliefs about foreign market offerings, as well as a higher inclination to buy imported products. For example, Ceballos et al (2018) showed that women have more favorable attitudes toward shopping from abroad, while Li et al (2021) reported that products purchased during a foreign country visit can be a means of selfexpression for women in their social lives when they go back to their own country. With regard to age, older consumers tend to use more information and are more careful when they consider purchasing products from foreign countries compared to their younger counterparts (Leonidou et al, 1999).…”
Section: Consumer Demographics and CImentioning
confidence: 99%
“…For many scholars in the West, it forms the most convenient way to unveil China and research multiple interesting issues of Chinese tourism (e.g. Chinese tourists’ taste, habit and behavioural pattern developed in travel, particularly, in face of an immense but still growing amount of money that they spend abroad) (see also Li et al , 2020). Their Chinese collaborators (or, more often, Chinese PhD students) are expected to provide insiders’ insights in the Chinese destinations under investigation.…”
Section: Patterns Of Chinese Tourist Gaze Studiesmentioning
confidence: 99%